VEGF: structure, biological activities, regulations and roles in the healing of diabetic ulcers - Nur Rosyid, Fahrun; Dharmana, Edi; Suwondo, Ari; Seno, Khristophorus Heri Nugroho Hario (International Journal of Research in Medical Sciences, 2018)
Diabetic ulcer patients can be hampered their ulcer healing process. The condition is caused by hyperglycemia and accumulation of advanced glycation end-products (AGEs) that can cause interference with VEGF and its receptors and signaling pathways. The VEGF core region is formed by a cystine bond motif with 8 invariant cystine residues in inter and intramolecular disulfide bound to the end of the central 4-stranded at each monomer with a side-by-side antiparallel orientation. VEGF stimulates angiogenesis in three dimensions, causing the encounter of microvascular endothelial cells, penetration into collagen gels and forming capillary-like structures. Regulation of VEGF gene expression through: (1) hypoxia; (2) cytokines and (3) differentiation and transformation. VEGF stimulates wound healing through several mechanisms such as collagen deposition, angiogenesis and epithelialisation.